Bone health in children with long–term idiopathic subclinical hypothyroidism - Di Mase, Raffaella (BioMed Central, 2012)
BACKGROUND: Subclinical hypothyroidism (SH) is a relatively common condition characterized by a mild persistent thyroid failure. The management of children with SH is still a controversial issue and the decision to treat with L-thyroxine represents a clinical dilemma. Thyroid hormone and TSH play an important role in skeletal growth and bone mineral homeostasis. AIM: To evaluate whether untreated idiopathic SH may affect bone health in childhood and to compare two different diagnostic tools such as dual-energy X-ray densitometry (DXA) and quantitative ultrasound (QUS). PATIENTS AND METHODS: Twenty-five children and adolescents (11 males) aged 9.8 ± 3.5 years (range 4.2-18.7) with untreated idiopathic SH were enrolled in the study. SH was diagnosed on the basis of normal FT4 levels with TSH concentrations between 4.2 and 10 mU/l. Children have been followed for 3.3 ± 0.3 years from the time of SH diagnosis. Twenty-five healthy children, age- and sex-matched, were enrolled as controls. Patients and controls underwent DXA to evaluate lumbar spine bone mineral density (BMD) and QUS at proximal phalanges of the non-dominant hand to assess bone quality, measured as amplitude-dependent speed of sound (Ad-SoS) and bone transmission time (BTT). RESULTS: Mean BMD Z-score was −0.4 ± 1.36 in patients and −0.2 ± 1.2 in controls. Mean Ad-SoS Z-score was 0.01 ± 1.0 in patients and 0.1 ± 1.2 in controls and mean BTT Z-score was −0.03 ± 0.8 and 0.04 ± 1.1 respectively. All values were within the normal range, both in patients and in controls. There were no statistically significant differences between the two groups. CONCLUSION: Bone health, evaluated by lumbar spine DXA and phalangeal QUS, is not impaired in our children, despite long-term duration of idiopathic SH. Data about bone status provided by QUS are comparable to those provided by DXA. Therefore, QUS may represent a good, cheaper and safe screening test for bone evaluation in children with SH.